(untitled) (Scientific journal of the Fergana State University, 2024)
The article is devoted to the theoretical foundations of the lexical system of language within the framework of syntagmatics and paradigmatics. The article examines the key concepts of paradigmatics and syntagmatics, as well as their interpretations in the works of such foreign linguists as Ferdinand de Saussure, Noam Chomsky and Louis Elemslev. The importance of these concepts for understanding the structure of language and the relationships between its elements is emphasized. The problems of studying paradigmatic and syntagmatic relations in the works of Russian linguists such as Lev Vladimirovich Shcherba, Nikolai Sergeevich Trubetskoy and Roman Jakobson are analyzed. The history of the development of theories about the syntagmatic-paradigmatic structure of the lexical system in Uzbek linguistics is considered. The works of such scientists as Berdaliev Abduvali, Mirzakulov Tursunali and Ziyaev Avaz are studied.